1992
DOI: 10.1002/bjs.1800790618
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of the intrathoracic stomach as an oesophageal substitute

Abstract: A study of duodenogastric reflux and gastric function was undertaken in 16 patients 1-7 years after oesophagectomy and high intrathoracic oesophagogastrostomy for oesophageal carcinoma. All were able to eat satisfactorily; ten complained of mild foregut symptoms and ten had endoscopic mucosal lesions. Biliary excretion scintigraphy demonstrated pathological duodenogastric reflux in 11 patients. The emptying of a semisolid radiolabelled meal from the intrathoracic stomach in the upright position was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 17 publications
2
48
0
2
Order By: Relevance
“…Thus, a positive Congo red test was found to be more common in patients with more than 5 years of follow-up than in those investigated earlier. 4 Likewise, comparison of data from two series of gastric transplant patients 2,3 indicates that the prevalence of cervical heartburn and endoscopic inflamma-tion in the esophageal remnant on the one hand and exposure of the latter to acid on the other are higher in patients with more than 1 year of follow-up than in those studied 6 to 12 months after surgery. Moreover, according to the well-known functional parallelism between the submucous and myenteric plexuses of the stomach, 5 the spontaneous motor recovery process we have found in the denervated whole stomach as an esophageal substitute 6,7 also bears out the hypothesis that acid secretion may recover with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a positive Congo red test was found to be more common in patients with more than 5 years of follow-up than in those investigated earlier. 4 Likewise, comparison of data from two series of gastric transplant patients 2,3 indicates that the prevalence of cervical heartburn and endoscopic inflamma-tion in the esophageal remnant on the one hand and exposure of the latter to acid on the other are higher in patients with more than 1 year of follow-up than in those studied 6 to 12 months after surgery. Moreover, according to the well-known functional parallelism between the submucous and myenteric plexuses of the stomach, 5 the spontaneous motor recovery process we have found in the denervated whole stomach as an esophageal substitute 6,7 also bears out the hypothesis that acid secretion may recover with time.…”
Section: Discussionmentioning
confidence: 99%
“…First, unlike antral motility, intraluminal acidity is not consistently reduced by total vagotomy, because one third of gastric transplant patients retained a normoacidic gastric pH profile just after surgery. 3 Second, although almost all patients recover a normal intraluminal pH profile beyond 3 years of follow-up, complete motor recovery, including the ability to generate phase 3 of the interdigestive motor complex, was observed in less than 50% of patients. 6 Third, unlike antral motility, recovery of a normal intraluminal acidity is not significantly influenced by resection of the lesser curvature for tubularization.…”
Section: Group 3 (N ‫؍‬ 42)mentioning
confidence: 99%
“…The earlier idea that the gastric tube is just an inert organ and that swallowed material just flows down due to gravity (Hinder, 1976;Moreno-Osset et al, 1986;Morton et al, 1991;Bonavina et al, 1992) has been changed to an acceptance that it can contract and demonstrate motor activity (Huang et al, 1985;Collard et al, 1998;Logeman et al, 2000). The construction of a gastric tube provides a functional replacement for both the esophagus and the stomach and gives the recipient a good quality of life (QOL) (Collard et al, 1998;Logeman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the fasting migrating motor complexes may occur late in follow-up in no more than half of the patients, 2,3 but the gastric tube was virtually inert after swallowing. 4,5 High-resolution manometry gives a detailed view that allows proper study of organs not conventionally studied by standard manometry in identifying the pressure impression of non-contractile anatomy structures, subtle peristalsis and flow obstructions. This technology is probably the most adequate to study the gastric tube after esophagectomy even though no previous studies focused on the topic.…”
mentioning
confidence: 99%